Tecnologia e educação: práticas sociais de escrita mediadas por vídeos do canal Nerdologia - Gomes, Gilmarques Lopes (2022)
The teaching-learning process needs to be rethought, a pedagogical praxis that aims only at a methodology based on outdated resources is no longer acceptable. Twenty-first century students are digital natives and fluent, however, schools end up not valuing digital technologies of communication and information in the learning process, creating an abyss between the student, who is immersed in a totally digital context, and teachers, most of which are from another century. Nor is it necessary to understand a school that does not see its members in an egalitarian way or at least that fully respects them, that provides a transformative education. Therefore, based on these reflections, we aim to understand how video as a pedagogical tool enhances learning, complements the teacher's discussion, transforms the simple transmission of information, enables critical analysis and the production of information, attracts the attention and interest of students and modernizes the teaching and learning process, creating equity, engagement, guaranteeing spaces for minority voice and protagonism. To discuss and guide us in this study, we rely on Freire (1997, 2003, 2001, 2011, 2018); Mollica (2007); Red (2013); Moran (1995, 2006); Perez Gomez (2015); Rojo and Moura (2012, 2019); Kleiman (2001); Soares (2020); Schneuwly and Dolz (2004, 2011); and many other authors. Among the results achieved with the research, we verified that: I ) the school and the teachers need to understand that the TDICs are allies in the teaching-learning process and that they will not replace the teacher; II ) the use of any technologies directed to the teaching of Portuguese language imprint modernity, engagement and collaboration between teachers and students for the development and improvement of the language; III ) the video translates into a dynamic and accessible teaching resource; IV ) digital literacy associated with language multisemioses contributed to the writing development of the students in this study.